2003
DOI: 10.2298/avb0303139n
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of left coronary artery branches in the African green monkey

Abstract: This study of distribution of the left coronary artery (LCA) in the African green monkey (Cercopithecus aethiops sabeus) was undertaken in order to determine the coronary artery epicardial network of this terrestrial primate. Insufficient data about these characteristics of LCA is a serious obstacle for widespread use of this species for experimental purposes. A total of 55 hearts from adult monkeys of both sexes (35 females and 25 males) was examined. These hearts were divided into two groups: group A corrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Similar to that reported in cat (Hadziselimovic et al., 1974; Cerny, 1976; Vladova, 2005), porcupine (Nickel et al., 1981), dog (Getty 1975), Syrian hamsters (Sans‐Coma et al., 1993), North American beaver (Bisaillon, 1981) and African green monkey (Valentina et al., 2003), the left coronary artery in the chinchillas also divides into two branches, the paraconal interventricular and left circumflex rami. On the contrary, it was reported that it gave rise to the left marginis ventricular, left posterior ventricular and septal rami in New Zealand rabbits (Aksoy and Karadag, 2002) or the paraconal interventricular, left marginis ventricular and left circumflex rami in rabbit (Day and Johnson, 1958).…”
Section: Discussionsupporting
confidence: 67%
“…Similar to that reported in cat (Hadziselimovic et al., 1974; Cerny, 1976; Vladova, 2005), porcupine (Nickel et al., 1981), dog (Getty 1975), Syrian hamsters (Sans‐Coma et al., 1993), North American beaver (Bisaillon, 1981) and African green monkey (Valentina et al., 2003), the left coronary artery in the chinchillas also divides into two branches, the paraconal interventricular and left circumflex rami. On the contrary, it was reported that it gave rise to the left marginis ventricular, left posterior ventricular and septal rami in New Zealand rabbits (Aksoy and Karadag, 2002) or the paraconal interventricular, left marginis ventricular and left circumflex rami in rabbit (Day and Johnson, 1958).…”
Section: Discussionsupporting
confidence: 67%
“…The right and left coronary arteries were present superficially to the epicardium and it was not observed deepening vessels in any of the animals as related in other species Sans Coma et al (1993), Bezerra et al (1985), Machado et al (2002). They are the heart suppliers, beginning in the right and left aortic sinuses, therefore, occupying the atrioventricular and interventricular coronary sulcus (Schummer et al, 1981;Ghoshal and Getty, 1986;Valentina et al, 2003;Oliveira et al, 2013) including in giant anteaters.…”
Section: Discussionmentioning
confidence: 99%
“…The heart is an organ with great functional importance, considering that a great amount of the human population suffers from functional problems which might require a transplant or These arteries can vary as to their origin, path and number (Schlesinger et al, 1949;Cervený and Kaman, 1963;Schummer et al, 1981;Ghoshal and Getty, 1986;Vicentini et al, 1991;Valentina et al, 2003;Olabu et al, 2007;Yuan et al, 2009;Agustin et al, 2010, Srour, 2011Kareem et al, 2014)) and they can be presented completely intramyocardial (Sans Coma et al, 1993) or partially (Bezerra et al,1985 andMachado et al, 2002). In instances where part of the artery is covered by the myocardium, structures called myocardial bridges can be observed and their functions are widely discussed (Berg, 1964 andCorban et al, 2014).…”
Section: Introduction mentioning
confidence: 99%
See 2 more Smart Citations